Awareness and perceptions towards sickle cell disease screening among young adults (18–45 years) at Mildmay Institute of Health Sciences, Wakiso District. A cross-sectional study. - Kobugabe, Ritah; Nansereko, Hasifa; Nalubega, Jane Frank; Naggulu, Ms. Immaculate Prosperia; Akankwasa, Edith (Student’s Journal of Health Research Africa, 2025)
Background Sickle cell trait prevalence ranges between 13% and 20%. The study aims to assess the prevalence of awareness and perceptions about sickle cell disease screening among young adults (18–45 Years) at Mildmay Institute of Health Sciences, Wakiso District. Methods A cross-sectional study design, which employed quantitative methods of data collection, was conducted in the Mildmay Institute of Health Sciences. In a duration of 6 days, 52 young adults (18–45 Years) were selected using Stratified random sampling. A structured questionnaire was used to collect data, and it involved closed-ended questions. The data collected was analyzed manually, and findings were entered into a Microsoft Excel 2013, which was then presented in the form of tables, pie-charts, and graphs. Results Out of 52 respondents, less than half, 34.6% were aged 31–35 years, and 50% were formally employed. About awareness, (90.4%) had never been tested for sickle cell disease nor had a family member tested, (73.1%) were unsure whether SCD is treatable, and (55.8%) reported receiving information about SCD screening through radio and television. Concerning Perceptions, 67.3% were unsure whether SCD screening is important for young unmarried youth, (73.1%), with reasons for not going for SCD screening as the emotional impact of the results. Conclusion Very few had undergone testing, and uncertainty about the treatability of the condition was prevalent and under perception; emotional fears, uncertainty about the importance of screening for unmarried individuals, and reluctance to test even under guaranteed privacy were major barriers. Recommendation SCD screening should be incorporated into the routine